Struktur Komunitas Makroalga di Perairan Jemeluk dan Penuktukan, Bali - Ni Wayan Ayu Astini Sari; I Dewa Nyoman Nurweda Putra; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2020)
This research was conducted at Jemeluk and Penuktukan water which have good marine resources with different environmental conditions. Jemeluk beach has reef flat zone and Penuktukan beach has reef slope zone. The aim of this research is to determin the comunity structure of macroalgae in Jemeluk and Penuktukan beach. The data of macroalgae comunity structure collected, use quadratic transect method with a size of 1x1 m placed following the line transect on the coral reefs with macroalgae along 25 meter. Identification of macroalgae using identification books from the Food and Agriculture Organization of the United Nation, The Living Marine Resources of the Western Central Pacific Volume 1: Seaweeds, Corals, Bivalves and Gastropods (FAO, 1998). The results showed that the percentages of macroalgae coverage in Jemeluk beach are found 6 genus of macroalgae with the highest percentage of coverage, density, and dominance of Halimeda (green algae). Simpson's dominance index in the Jemeluk waters is in a low dominance index and diversity is in the medium Shannon-Wiener diversity index. Furthermore Penuktukan beach found 5 genus of macroalgae with highest percentage of cover, density, and dominance by Gracilaria (red algae). Simpson's dominant index in this wates is in the low category and the macroalgae diversity from all stations was in the category of the medium Shannon-Wiener diversity index too.